The use of GPS for continuous measurement of kinematic data and for the validation of a model in alpine skiing - Seifriz, F.; Mester, J.; Kraemer, A.; Roth, R. (International Journal of Computer Science in Sport, 2002)
At the Institute for Theory and Practice of Training and Movement a model was developed to calculate the running time and the optimal trajectory in alpine skiing with the use of genetic algorithms. Up to now the results of the validation of the model were promising but the evaluation (3D-kinematic, DLT) required a lot of time. A GPS-System from the Institute for Sports and Environment offers new possibilities to measure kinematic data of alpine skiers and could be used to validate the model of alpine skiing. The advantage of this GPS-System is the direct use of the results without time-consuming calculations. Further the data of the GPS-System could be used to produce virtual camera rides and to evaluate the results under aspects of competition and aspects of safety (e.g. comparison between real and optimized trajectories, analysis of the curve radius, analysis of the angle of gate entrance, analysis of the centrifugal force). The aim of the study was to prove the practical use of this GPS-System in alpine skiing. The DGPS-System SR 530 (Leica) works with a differential phase correction and reaches an accuracy of ±1 cm. It is also possible to measure in a kinematic mode with 10 Hz. We used two antenna systems: the original antenna with differential phase correction (fixed on the helmet) and very small antenna without differential phase correction (fix on a ski). The results of the GPS measurement were compared with the data of a 3D-video-kinematic (DLT). Based on the number of used satellites the GPS-System calculates an accuracy range for each data point. In case of the antenna with differential phase correction and 10 Hz sampling rate in kinematic mode we get data with an accuracy of 1-5 cm under normal skiing conditions. Without the differential correction the quality of the measured data get worse up to a few meters. The reasons therefore are: first the lack of the differential phase correction and second if the ski is edged also the antenna is edged and this leads to a loss of satellites which are necessary to get the right position and to increase the accuracy of the measurement. Due to the fixation on the helmet there is a difference between the GPS data and the real trajectory of the ski. The comparison with the 3D-video-kinematic clearly shows these differences depending on the curve and the body posture. Overall the investigation showed that it is possible to record with a DGPS-System kinematic data of a skier with an accuracy of a few centimeters. Further it is necessary to develop smaller antenna with differential correction, so that it is possible to place it direct on the ski to reduce the error of measured data and real trajectory.